PENDAMPINGAN PEMBIASAAN DO’A BERSAMA PADA AWAL PEMBELAJARAN DALAM PENINGKATAN KEDISIPLINAN SANTRI TPQ DARUL IHSAN KABUPATEN TUBAN: ASSISTANCE OF HAPPYING TOGETHER PRAYER AT THE BEGINNING OF LEARNING IN IMPROVING DISCIPLINE OF TPQ DARUL IHSAN STUDENTS, TUBAN REGENCY - Farida Isroani; Fahru Rozi; Ulva Badi Rahmawati (STIK KESETIAKAWANAN SOSIAL INDONESIA, 2020)
Character education for students is very important to be taught and exemplified from an early age. The application of disciplined education will be maximized if by applying it in everyday life. As well as the implementation of prayer at the beginning of learning. This study aims to determine how the conception and implementation of prayer together at the beginning of learning in increasing the discipline of Darul Ihsan TPQ students, Simo Village, Soko District, Tuban Regency. This research is a qualitative research with the technique of colleting observation data, interviews and documentation. While the data analysis techniques used were data reduction, data presentation and conclusions. It can be concluded that praying together at the beginning of learning in improving the discipline of TPQ Darul Ihsan students, Simo Village, Soko District, Tuban Regency uses several ways, namely regulations, advice, punishment, and giving example. Then the results of the implementation of joint prayer et the beginning of learning are that students are more responsible, behave well, bring disciplined character in the community, students are easy to remember, apply the discipline of praying before doing work, students become more enthusiastic about the koran. As for the supporting factors, there are punishments and obstacles lack of support from family.